Alternativas de control quimico de malezas anuales en Mentha piperita L. - Darre, C.A.=700 1 Novo, R.J.; Zumelzu, G.; Bracamonte, E.R.
(Es, En)
ilus., 6 ref.
Keywords: MENTHA PIPERITA; CONTROL QUIMICO; MALEZAS; HERBICIDAS; FITOTOXICIDAD; ARGENTINA; SELECTIVIDAD